American Alligator - Gray, Susan Heinrichs (Ann Arbor, Mich. : Cherry Lake Pub., 2008)
Explains how alligators became endangered and describes successful efforts to help them survive and increase.
Includes bibliographical references (p. 31) and index.
Keywords: Alligators